The Effect of Flowrate and Effectiveness on Theoretical Design and Thermal Characteristic of a GHE - Mohd Yusof, Taib; F., Basrawi; Shahrani, Anuar; Hassan, Ibrahim (MATEC, 2018)
Ground heat exchanger is an exciting technique to reduce energy consumption in building especially in hot climate countries. Implementation of GHE for commercial unit in Malaysia is almost none in record. Thus, performance study of the GHE in Malaysia is crucial to be conducted either experimentally or numerically. Therefore, this paper presents the performance of GHE in term of effectiveness, outlet temperature and rate of heat transfer based on mathematical model. The model is developed based on cross flow heat exchanger with one fluid unmixed. There are two variable parameter used in the analysis which is effectiveness and flowrate of the air for 25 meter length of a PVC pipe. Three effectiveness values which is 0.8, 0.9 and 0.99 have been analysed in this study. Meanwhile, flowrate of air is ranging from 0.02 to 0.2 kg/s. Results show that flowrate at 0.02 kg/s gives great temperature reduction in the pipe compared with higher flowrate. However, flowrate of 0.2 kg/s produces higher cooling potential. Characteristic of the GHE for the rate of heat transfer with 80, 90 and 99 percent effectiveness also have been developed and it has been found that effectiveness of 0.9 provide good combination between flowrate and the rate of heat transfer for 25 meter length of the pipe.